1995
DOI: 10.1038/373438a0
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine T-cell suicide mediated by APO-1/(Fas/CD95)

Abstract: The APO-1/(Fas/CD95) cell surface receptor is a member of the nerve growth factor (NGF)/tumour necrosis factor (TNF) receptor superfamily and mediates apoptosis. Peripheral activated T cells (ATC) from lymphoproliferation (lpr/lpr) mutant mice that express a reduced number of APO-1 receptors have a defect in T-cell receptor (TCR)-induced apoptosis. This suggests that TCR-induced apoptosis involves APO-1. We tested this hypothesis in various human T cells: (1) malignant Jurkat cells, (2) an alloreactive T-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

45
997
2
15

Year Published

1995
1995
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,549 publications
(1,061 citation statements)
references
References 24 publications
45
997
2
15
Order By: Relevance
“…Activation of T lymphocytes increases their expression of Fas and induces their expression of Fas-L within 24 h, and they become susceptible to Fasmediated apoptosis 3-4 days after activation (Brunner et al, 1995, Ju et al, 1995and Dhein et al, 1995. The ligation of Fas on the surface of the T cell can be mediated by Fas-L on the same T cell or by Fas-L expressed by other cells (Brunner et al, 1995 andDhein et al, 1995). Using four-colour flow cytometry on lymphocytes extracted from GBM, we have shown that T cells expressing Fas-L are 8 times more likely to undergo apoptosis than those not expressing Fas-L.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of T lymphocytes increases their expression of Fas and induces their expression of Fas-L within 24 h, and they become susceptible to Fasmediated apoptosis 3-4 days after activation (Brunner et al, 1995, Ju et al, 1995and Dhein et al, 1995. The ligation of Fas on the surface of the T cell can be mediated by Fas-L on the same T cell or by Fas-L expressed by other cells (Brunner et al, 1995 andDhein et al, 1995). Using four-colour flow cytometry on lymphocytes extracted from GBM, we have shown that T cells expressing Fas-L are 8 times more likely to undergo apoptosis than those not expressing Fas-L.…”
Section: Discussionmentioning
confidence: 99%
“…While most receptors of this family are implicated in proliferative processes, TNF receptor and Fas, when cross-linked by antibodies or their physiological ligands (TNF or the Fas ligand, respectively), frequently induce apoptosis [2][3][4][5]. TNF has a main role in inflammatory responses [4] while Fas-mediated apoptosis participates in the effector function of cytotoxic T-lymphocytes [6,"], as well as in the auto-elimination of activated mature T-~ells, and hence, in peripheral tolerance [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This results in shedding of the receptor-binding FasL ectodomain (referred to as soluble Fas ligand (sFasL)), the biological role of which is still disputed (reviewed in 1 ). sFasL can either cause apoptosis at a distant site 6,7 or alternatively dampen the apoptotic response by blocking Fas receptors. 8,9 The fate of the remaining membrane-anchored N-terminal portion of FasL, which comprises a transmembrane region and the proline-rich FasL intracellular domain (FasL ICD), has not been studied so far.…”
mentioning
confidence: 99%